La Serena cheese (Spain), development of an area based on Merino ewe breeding - López Gallego F.; Morillo Nieto C. (L'Observatoire des Systèmes de Production Ovine et Caprine en Méditerranée : Chiffres clés et indicateurs de fonctionnement et d'évolution, 2002)
La Serena is a large area in Extremadura (the southwest of Spain) where merino ewe cheese is produced. Cheese production has revolutionised the whole ovine sector in this area. This ovine sector is the most important economic factor in La Serena. It contributes decisively to the development of this rural area. Such development is due to the Merino ewe cheese making. In order to contribute to the economic development, guidelines have been carried out by the Farming Regional Institutions together with the European Union: commercial and productive structure; technological updating; adaptation to the EU regulations; quality control, training, investments and marketing financing.